Cyberattacks: The latest threat to international peace and security, and how international law can respond - Tlhacoane, Tshepo (Department of Public Law, 2021)
Today it is accepted that states may not unilaterally attack each other using rifles, missiles, nuclear, or chemical weapons. But what about computer software such as worms and trojans which are capable of causing similar or greater damage? Are states permitted to attack each other using these so-called cyberweapons? Are they even considered weapons due to their differing form? This is the crux of what this dissertation is about. It aims to show that if states are prohibited from attacking each other with certain categories of weapons, they should not be permitted to attack each other with a different weapon which causes similar damage. I make three overarching arguments in this dissertation. The first is that cyberweapons should be considered ‘weapons' even though they differ in form and sophistication. Secondly, that the use of cyberattacks is a use of force and contravenes article 2(4) of the UN Charter. Finally, I will argue that extant international law is not able to maintain international peace and security and that a multilateral treaty is required.